Pengakuan Pendapatan Dan Beban Pengaruhnya Terhadap Laba Pada Asuransi Jiwa Bersama Bumi Putera 1912 - Herawati, Heti (Jurnal Ilmiah Ranggagading (JIR), 2001)
Asuransi Jiwa Bersama Bumi Putera is an enterprise moving in insurance field. The problem of revenue acknowledgement and the companyâs expenses not only influenced by the matters f accounting alone, but also by the government regulations in insurance extent. The regulation affected the amount of the companiesâ allowance of technical reserves. On the other hand , life insurance company also influence company by the problem of risk uncertainty which the company must report.